Porn as Queer(ing) Feminist Utopia. Pornotopia Revised - Held , Sarah; Sadzinski, Sylvia (Göttingen, 2026)
Shown from 31 March to 4 May 2022, the exhibition pornotopia revised at Kunsthalle Exnergasse in Vienna explored the interstice of art and post-porn in its visual and material culture. The exhibition showed contemporary works that deal with desire, sexuality, and their representations and demonstrate the grey area between porn and art. Therefore, pornotopia revised was not limited to audiovisual explorations: contemporary sculptures, paintings, and video works in the so-called Porno Plüsch Platzerl [Porn Plush Place] reflected on narratives and representations of bodies and desire. The overall focus was not primarily on voyeurism or provocation through nudity or sexual acts, but on resistance and emancipation. The artistic works took up moments from porn, queered them or used them, for example, to debate the categorization, sexualization, and objectification of bodies and to question norms around sexuality and gender binary. The exhibition deliberately played with readings and aesthetics between so-called high and low culture, between trash, kitsch, and minimalism, between analogue craft and digital expression.
Keywords: Pornografie; Kunst; Queer Feminist Curating; Queer Feminist Exhibition-Making; Sexuality; Post-Porn; Bodies; Desire; Emancipation